Web-Based Campus Facility Loan Application Using CodeIgniter 4 - Fitrotuzzahwannisa' Fitrotuzzahwannisa'; Siti Sufaidah; Munawarah Munawarah (NEWTON: Networking and Information Technology, 2026)
The conventional process of campus facility borrowing often leads to delays in information delivery and difficulties for users in understanding facility availability. In addition, the presentation of borrowing schedules in non-visual formats makes it challenging for users to quickly interpret facility usage status. This study aims to design and develop a web-based campus facility borrowing application that provides visual schedule information and supports a fully digital submission process. The system development employs the Software Development Life Cycle (SDLC) using the Waterfall model, which consists of requirement analysis, system design, implementation, and testing stages. The application is developed using the CodeIgniter 4 (CI4) framework, PHP programming language, and MySQL database. System testing is conducted using the black-box testing method to ensure that all system functions operate according to user requirements. The results indicate that the developed system successfully simplifies the campus facility borrowing process, presents borrowing schedules through a visual calendar interface, and clearly displays submission status and borrowing history. These features improve efficiency, transparency, and accessibility in the management of campus facility borrowing.